International research for the betterment of children worldwide: Early Childhood Education: International Research Report (2015). Editor: Dr. László Varga University of West Hungary, Benedek Elek Faculty of Pedagogy, Sopron, Hungary (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2015)
The book “Early Childhood Education: International Research Report” edited by László Varga is a unique and successful demonstration of global efforts for the betterment of children worldwide. This joint research initiative brought researchers and practitioners from the field of early childhood together to explore the context and culture of childhood as perceived by children, and current and future educators. In sixteen chapters, authors from eight countries across three continents – Europe, Asia and America – investigated diverse aspects of childhood and child development, such as children stories, play, project approach and traditional and non-traditional learning environments. The purposeful selection of countries and authors allows the reader to gain insights into early childhood trends and practices in diverse cultures. The studies conducted in various countries – Croatia, Czech Republic, Greece, Spain, Turkey, The United Kingdom, Thailand and the United States of America – target the local context of childhood; however the context-specific findings carry features of similarities